Representasi Nilai Karakter dan Kehidupan Sosial Perempuan Arab Saudi dalam Film from The Ashes - Yosep Fatahudin; rohanda rohanda; khomisah khomisah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
This study aims to analyze the representation of character education values and the social dynamics of Saudi Arabian women in the film From the Ashes through Charles Sanders Peirce’s semiotic approach. The study is motivated by the limited number of semiotic studies examining the representation of Saudi women in contemporary Middle Eastern cinema, particularly those connecting cinematic signs with character education and social transformation within educational settings. Previous studies have primarily focused on cultural and feminist perspectives, leaving the relationship between symbols, social meanings, and women’s identity transformation insufficiently explored. This research employs a descriptive qualitative method using Peirce’s semiotic framework by identifying icons, indexes, and symbols embedded in scenes, dialogues, character expressions, costumes, and social settings portrayed in the film. Data were collected through direct observation of the film available on Netflix and analyzed based on the relationship between sign, object, and interpretant. The findings reveal that the film represents character education values through symbols of moral courage, responsibility, female solidarity, and critical attitudes toward social pressures within educational environments. Furthermore, the film portrays Saudi women as negotiating between patriarchal traditions and modernity, reflected in school spaces, institutional regulations, social interactions, and visual depictions of social control. The novelty of this study lies in its semiotic interpretation of Saudi women’s representation through the lens of character education and social change. This research contributes to expanding film semiotics studies by highlighting the role of cinema as a medium for constructing social meaning and reflecting cultural transformation in contemporary Arab society.